Optimal Contracts with Hidden Information: An Export Consortium Case - Alderete, Maria Veronica (2011)
This paper analyzes the creation of an export consortium among small and medium sized enterprises (SME) by the State. A hidden information principal agent model is introduced to explain the presence of SME export consortiums. The State (principal) can not observe the random realization of the firm’s (agent) disutility from effort. We introduce a setting where the informational asymmetry is post-contractual. The contract specifies the subsidy and effort levels that result from different announcements of the state by the firm. By means of the subsidy payments, the revelation of firms’ competitiveness can be achieved. The results obtained are that subsidies are ex post inefficient and they can constraint the participation of the less competitive firms to the export consortium.